STRATEGI EVALUATIF DALAM REPRESENTASI WACANA POPULISME PADA PIDATO KAMPANYE PEMILIHAN CALON PRESIDEN ANIES BASWEDAN - Dede Fatinova; eris risnawati (Epigram, 2026)
The discourse of populism is a political issue that frequently discussed in a global context. As an phenomenon that is closely related to language use, populism has rarely been examined through linguistic analysis, particularly in Indonesia. This study aims to reveal how discourse of populism is constructed through specific language strategies. The data consist of Anies Baswedan's speech delivered during the 2024 Presidential Campaign, obtained from documentation on YouTube. The data in this study was analyzed using a Systemic Functional Linguistics approach that focuses on the Attitude system within the Appraisal analysis framework (Martin & White, 2015). The results of this study show that the construction of populist discourse is explicitly realized through Attitudinal resources that focus on affect, judgment, and appreciation. The emergence of a dichotomous narrative between the people and the elite is realized through the use of affect and judgment, while the emergence of narratives of crisis, destruction, and threat is realized through the use of appreciation, more specifically referring to negative appreciation-valuation. These findings indicate that evaluative language has a role in constructing populist discourse in the political sphere in Indonesia.